Implementation of Marketing Mix Strategies in Dealing with Business Competition in The Islamic Economy’s Perspective : Penerapan Strategi Bauran Pemasaran dalam Menghadapi Persaingan Bisnis dalam Perspektif Ekonomi Islam - Septya Rifki Ayunda Paramesta; Masruchin (Universitas Muhammadiyah Sidoarjo, 2021)
An important marketing strategy is carried out by a business so that it does not lag behind its competitors, of course it must be carried out in accordance with marketing in Islamic sharia. In the face of competition, Martabak Terangbulan Bogasari Bandung implements a marketing mix strategy. This research uses case study qualitative research method. Data collection techniques used through interviews, observation, documentation and questionnaires. The informants of this research are business owners, supervisors, outlet employees and consumers of Martabak Terangbulan Bogasari Bandung. The results of this study, the marketing mix strategy applied by Martabak Terangbulan Bogasari Bandung in the face of competition includes product strategy, price, place, promotion, people (employees), process and physical evidence. These strategies include making quality products, providing menu variants, setting affordable prices, strategic outlet locations, opening branch outlets, promoting on social media and offering purchases through Gofood. The marketing mix strategy used by Martabak Terangbulan Bogasari Bandung is not in accordance with Islamic sharia. The discrepancy can be seen from the behavior of employees who smoke while serving purchases.